Evidence-based Clinical Practice Guidelines for Hepatocellular Carcinoma: The Japan Society of Hepatology 2013 update (3rd JSH-HCC Guidelines) - Kokudo, Norihiro; Hasegawa, Kiyoshi; Akahane, Masaaki; Igaki, Hiroshi; Izumi, Namiki; Ichida, Takafumi; Uemoto, Shinji; Kaneko, Shuichi; Kawasaki, Seiji; Ku, Yonson; Kudo, Masatoshi; Kubo, Shoji; et al. (Hepatology research, 2015)
The 3rd version of Clinical Practice Guidelines for Hepatocellular Carcinoma was revised by the Japan Society of Hepatology, according to the methodology of evidence‐based medicine, which was published in October 2013 in Japanese. Here, we briefly describe new or changed recommendations with a special reference to the two algorithms for surveillance, diagnosis, and treatment.